Soil dust aerosol in the atmosphere: sources, quantities, properties (overview) - A. Yu. Romanovskaya; I. Yu. Savin (Бюллетень Почвенного института им. В.В. Докучаева, 2021)
Dust is a major component of atmospheric aerosols – 75% of the global aerosol load. Natural and anthropogenic sources are listed, as well as dust research methods. According to different estimates, the average mineral dust load in the atmosphere ranges from 20 to 33 Tg, and the annual dust emission is 1 200–5 900 Tg/year. Reports from the Intergovernmental Panel on Climate Change (IPCC) inform about the total direct radiative forcing of dust ranging from -0.56 to +0.1 W/m2, with little scientific understanding of the processes leading to this result. The particle size, including soil aerosol, is divided into fine (<5 μm), medium (5–10(20) μm) and coarse (>20 μm) dust. Fine dust cools the global climate due to dispersion of solar radiation, while coarse dust (greater than 5 μm) warms the climate by absorbing solar and thermal radiation. However, the coarse dust (above 20 μm) remains poorly investigated, with very little data on its content and emission. Recent studies suggest that coarse dust (17 Tg), missed by the global models, contributes on average 0.15 W/m2 (0.10 to 0.24 W/m2) to atmospheric heating and also affects the global distribution of clouds and precipitation. In addition, soil dust is characterised by a complex and diverse particle shape and structure, heterogeneous mineralogical and chemical composition; due to its dispersion ability and large surface area dust reacts with other types of aerosols, resulting in the formation of different films on the particle surface or internal mixing. All this significantly changes the optical properties of mineral dust and complicates the development of models for its investigation.